Cloning and sequence analysis of the growth hormone gene in Indian elephants - Bhosale R A (Department of Animal Breeding, Genetics and Biostatistics, College of Veterinary and Animal Sciences, 2009)
The study was undertaken with the objectives of cloning and sequence analysis of the growth hormone gene of the Indian elephants. The growth hormone is a peptide hormone produced in the anterior pituitory. It stimulates the growth of vertebates. It is a protein hormone of about 190 amino acids, synthesized and secreted by cells called somatotrophs. Growth hormone is a major participant in the control of several complex physiologic processes, including growth and metabolism and it is also of considerable interest as a drug used in both humans and animals. The genomic DNA was isolated from blood samples and a 1712 bp fragment of the entire transcriptional unit of the GH was amplified by PCR using synthetic oligonucleotide primer pair designed based on the 5′ and 3′ flanking sequences of goat growth hormone gene. The gel purified PCR product was ligated in to the pGEM®-T Easy cloning vector and was transformed by giving heat shock to competent E. coli cells prepared by CaCl2 treatment. The recombinant clones among the transformed cells were identified by Blue–White Screening and the recombinant plasmid carrying the insert gene was isolated from the white clones by a modified SDS-alkaline lysis method. The 1.712 kb GH gene insert in the vector was sequenced by the dideoxynucleotide sequencing method with primer walking using an automated DNA sequencer. The nucleotide sequence showed 75 to 96 per cent homology with pig and 77 to 95 per cent with that of Dolphin GH genes, respectively. The exon-intron boundaries in the porcine gene occur at the codons of the amino acid residues, Gly-4 (intron 1), Phe-57 (intron 2), Ser-96 (intron 3) and Arg-150 (intron 4). The all four residues are conserved in both species and also in African elephants. This strict homology in the sites of insertion of introns suggests that the exon-intron organization of these genes was established before the divergence of these species. The positions of the exon-intron boundaries are also conserved as evidenced from similar sizes of the exons. Evidence for some homology was also seen in intron 1, which showed maximum 84 per cent similarity with giraffe. In contrast, intron 2, 3 and 4 showed no significant similarity both in length and in sequence with other animal species. The Indian elephant GH gene has an open reading frame of 648 nucleotides encoding a signal peptide of 26 amino acid residues and a mature protein of 190 amino acid residues with both NH2- and COOH- terminal phenylalanine. Alignment of this sequence with African elephant counterpart showed that 189 amino acid residues are identical with only one variant while, with pig sequence it showed 186 identical residues with four variants. The predicted secondary structure showed that the larger α-helical lobe is formed by four sections of the polypeptide chain (residues 3-34, 47-80, 110-126 and 148-172) while the smaller lobe, which encompasses a small antiparallel beta-sheet and a small irregular structure formed the remaining structure of the polypeptide chain. The predicted tertiary structure of the Indian elephant GH showed high homology with the human GH structures. Overall, the structures of Indian elephant GH gene was found to be very similar to that of African elephant and porcine reflecting their high degree of amino acid sequence identity (99 – 97 per cent).